Parkett - 20 Years of Artists' Collaborations - Burckhardt, Jacqueline; Curiger, Bice; von Graffenried, Dieter; Varadinis, Mirjam (Zürich : Parkett Publishers, 2004)
The art magazine Parkett was inspired by the idea of not merely reporting on artists, but also working in close collaboration with them and having them produce original contributions for each volume. 2004 sees Parkett celebrating its 20th anniversary. For this occasion, the Kunsthaus Zürich has mounted an exhibition entitled Parkett - 20 Years of Artists' Collaborations, presenting the entire set of artists' editions created since 1984. This catalogue, in English and German, explores a 10-year success story and allows readers a privileged view behind the scenes. An exhaustive interview with Parkett's creators yields an Oral History illustrated with never-before seen photographs and pictures from the Parkett archive. Unpublished letters, sketches and faxes from those 150 artists who have worked with Parkett so far vividly demonstrate the creative processes that go into the production of the magazine's issues and editions. Short statements by international artists, curators, collectors and others complete the personal story of Parkett over the past two decades.
Ackermann, Franz ; Ahtila, Eija-Liisa ; Aitken, Doug ; Alys, Francis ; Anderson, Laurie ; Armleder, John M. ; Artschwager, Richard ; Bächli, Silvia ; Baldessari, John ; Balkenhol, Stephan ; Barney, Matthew ; Baselitz, Georg ; Beecroft, Vanessa ; Bleckner, Ross ; Bock, John ; Alighiero e Boetti ; Boltanski, Christian ; Bourgeois, Louise ; Breuning, Olaf ; Bulloch, Angela ; Buren, Daniel ; Calle, Sophie ; Cattelan, Maurizio ; Celmins, Vija ; Clemente, Francesco ; Close, Chuck ; Cucchi, Enzo ; Currin, John ; Dean, Tacita ; Demand, Thomas ; Disler, Martin ; Doig, Peter ; Dumas, Marlene ; Eliasson, Olafur ; Emin, Tracey ; Fischl, Eric ; Fischli & Weiss ; Fleury, Sylvie ; Förg, Gunther ; Friedman, Tom ; Fritsch, Katharina ; Genzken, Isa ; Gertsch, Franz ; Gilbert & George ; Gillick, Liam ; Gober, Robert ; Goldin, Nan ; Gonzalez-Torres, Felix ; Gordon, Douglas ; Graham, Dan ; Graham, Rodney ; Gursky, Andreas ; Hammons, David ; Hirschhorn, Thomas ; Hirst, Damien ; Holzer, Jenny ; Horn, Rebecca ; Horn, Roni ; Hume, Gary ; Huyghe, Pierre ; Kabakov, Ilya ; Kapoor, Anish ; Katz, Alex ; Kawara, On ; Kelley, Mike ; Kelly, Ellsworth ; Kentridge, William ; Kilimnik, Karen ; Kippenberger, Martin ; Knoebel, Imi ; Koons, Jeff ; Kounellis, Jannis ; Kusama Yayoi ; Laib, Wolfgang ; Levine, Sherrie ; Lucas, Sarah ; Marclay, Christian ; Marden, Brice ; Merz, Mario ; Moffatt, Tracey ; Mori, Mariko ; Morley, Malcolm ; Morris, Sarah ; Muñoz, Juan ; Mylayne, Jean-Luc ; Nauman, Bruce ; Noland, Cady ; Oppenheim, Meret ; Orozco, Gabriel ; Oursler, Tony ; Owens, Laura ; Pardo, Jorge ; Pettibon, Raymond ; Peyton, Elizabeth ; Phillips, Richard ; Polke, Sigmar ; Prince, Richard ; Raedecker, Michael ; Raetz, Markus ; Ray, Charles ; Rhoades, Jason ; Richter, Gerhard ; Riley, Bridget ; etc.
Editionen = Editions 1984-2004 p. 196-209
Duits
Engels
Exhibition. Parkett - 20 years of artists' collaborations. Kunsthaus Zürich. 2004-11-26. 2005-02-13
boek